Duckling Production —A profitable enterprise for rural youth - Roy, Rakesh; Sarkar, Ashim (Indian Farming, 2022)
Entrepreneurship development through duckling production with low-cost incubator is a promising enterprise that can be a good source of income for the unemployed rural youth. Economic analysis has shown that the enterprise has the potential to provide year-round employment to the rural youth with good remuneration if proper care and management during incubation and brooding of ducklings is done.